Major approaches to dental implants in the biological environment of bone regeneration: a systematic review - Camargo, Kamila Stellita Teixeira de (2023)
Introduction: The presence of sufficient bone volume, both in width and height, is crucial for adequate implant placement and osseointegration, allowing stability of the peri-implant hard and soft tissues. Several bone augmentation techniques can be performed to preserve or reconstruct a resorbed alveolar ridge or pneumatized maxillary sinus. Bone remodeling of the ridge and buccal bone will still occur after tooth removal. Objective: It was to develop a systematic review to present the main approaches to dental implants in the biological environment of bone regeneration. Methods: The present study was followed by a systematic review model (PRISMA). The search strategy was performed in the PubMed, Cochrane Library, Web of Science Scopus, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: A total of 123 articles were found involving implantology and biomaterials. A total of 48 articles were fully evaluated and 34 were included in the systematic review. A total of 26 studies were excluded because they did not meet the GRADE criteria, and 22 studies were excluded because they had a high risk of bias. The symmetric funnel plot does not suggest a risk of bias between the small sample size studies. It was concluded that the search for a solution for large bone defects guided studies toward tissue regeneration therapy or bone regeneration. These studies can promote the use of fillers and epithelial barriers that assist in treatment as adjuvants to bone grafting techniques. Understanding host biological niche processes of signaling for neovascularization and bone regeneration and filling is necessary for subsequent dental success. Furthermore, implants placed in tobacco users, as well as in enlarged maxillary sinuses, simultaneously or in stages, and enlarged ridges lead to higher rates of implant failure.